Ion adsorption-induced reversible polarization switching of a van der Waals layered ferroelectric - Dong-Dong Xu (Nature Portfolio, 2021)
Whether it is possible to achieve polarization inversion in a ferroelectric without any energy consumption is an open question. Here, the authors demonstrate an energy-free approach to control the polarization state of CuInP2S6, a typical room-temperature van der Waals layered ferroelectric.